PENERAPAN METODE BERMAIN BERBANTUAN KARTU HURUF BERGAMBAR UNTUK MENINGKATKAN IMAJINASI DAN KETRAMPILAN MENULIS AWAL - Sinta Yulia (DIADIK, 2023)
This study aims to explain 1) increase children's imagination power 2) the application of the picture card-assisted playing method in children 3) the effectiveness of the application of picture card-assisted games in writing skills in the children of Group B Baitul Ilmi Kindergarten, Bengkulu City. The research design is a mixed methods research. The sample in this study is for the CAR class that will be given the play method treatment is consists of 10 children. 10 children as the experimental class and the control class with a total of 10 children. Data collection techniques in this study used: 1) observation, 2) tests and the results of children's work. The results were as follows: 1) The results of children's early writing skills in cycle II increased significantly when compared to writing abilities in cycle I, 2) Results of early writing skills in cycle III increased significantly when compared to the writing ability in cycle II, 3) The results of the child's early writing ability in cycle III increased significantly when compared to writing ability in cycle I. Research proves that the application of the illustrated letter card playing method is more effective than the conventional method approach